THE INFLUENCE OF THE SCHOOL LITERACY MOVEMENT ON EARLY READING SKILLS - Putri Saridewi; Gilang Gumilang Dawous; Ibnu Imam Al Ayyubi (El Midad, 2025)
This research aims to determine the influence of the School Literacy Movement on reading ability at the beginning of grade 1 at MI Karanganyar. The method used in this research is a quantitative method with a survey research design and data collection techniques using questionnaires. The sample in this study consisted of 35 students. The results of the research show that there is no significant correlation between familiarization with school literacy movements and initial reading ability, with PTS data correlation test values ??of 0.217 and 0.225 and PAS data correlation test values ??of 0.102 and 0.570. Based on the research results, it can be concluded that there is no statistically significant relationship between these two variables. Thus, to increase the effectiveness of literacy programs and early reading skills, more systematic and targeted efforts are needed in implementation, as well as continuous monitoring and evaluation to ensure that program objectives can be achieved well. Addressing irregularities in implementation, increasing resources and supports, and reducing variability in individual responses can help strengthen the relationship between early reading skills and school literacy movement practices.